SMAD4 mutations found in unselected HHT patients. Issue 10 (13th April 2006) - Gallione, C J; Richards, J A; Letteboer, T G W; Rushlow, D; Prigoda, N L; Leedom, T P; Ganguly, A; Castells, A; Ploos van Amstel, J K; Westermann, C J J; Pyeritz, R E; Marchuk, D A
Abstract : Background: Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant disease exhibiting multifocal vascular telangiectases and arteriovenous malformations. The majority of cases are caused by mutations in either the endoglin ( ENG ) or activin receptor-like kinase 1 ( ALK1, ACVRL1) genes; both members of the transforming growth factor (TGF)-β pathway. Mutations in SMAD4, another TGF-β pathway member, are seen in patients with the combined syndrome of juvenile polyposis (JP) and HHT (JP-HHT). Methods: We sought to determine if HHT patients without any apparent history of JP, who were undergoing routine diagnostic testing, would have mutations in SMAD4 . We tested 30 unrelated HHT patients, all of whom had been referred for DNA based testing for HHT and were found to be negative for mutations in ENG and ALK1 . Results: Three of these people harboured mutations in SMAD4, a rate of 10% (3/30). The SMAD4 mutations were similar to those found in other patients with the JP-HHT syndrome. Conclusions: The identification of SMAD4 mutations in HHT patients without prior diagnosis of JP has significant and immediate clinical implications, as these people are likely to be at risk of having JP-HHT with the associated increased risk of gastrointestinal cancer. We propose that routine DNA based testing for HHT should include SMAD4 for samples in which mutations in neither ENG nor ALK1 are identified. HHT patients with SMAD4 mutations should be screened for colonic and gastric polyps associated with JP.